2000
DOI: 10.1088/0022-3727/33/21/320
|View full text |Cite
|
Sign up to set email alerts
|

A collisional radiative model for mercury in high-current discharges

Abstract: A collisional radiative model is presented for mercury discharges with electron temperatures between 0.75-2 eV and electron densities between 1018-1020 m-3. Such plasma parameters are encountered in a number of modern light sources, such as mercury-operated induction lamps and the compact fluorescent lamp. The analytical top model has been used, which allows the majority of the non-equilibrium levels to be taken into account implicitly. As a result, indirect ionization processes involving highly excited atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These deviations decrease for higher electron densities [12,13], since the progressively increasing influence of the electron-electron Coulomb collisions will impose a Maxwellian EEDF. In forthcoming work [15] it will be shown that for electron densities above 10 19 m −3 the deviations from Maxwell are negligible.…”
Section: Argon Metastable Densitymentioning
confidence: 91%
See 2 more Smart Citations
“…These deviations decrease for higher electron densities [12,13], since the progressively increasing influence of the electron-electron Coulomb collisions will impose a Maxwellian EEDF. In forthcoming work [15] it will be shown that for electron densities above 10 19 m −3 the deviations from Maxwell are negligible.…”
Section: Argon Metastable Densitymentioning
confidence: 91%
“…The ionization coefficient of mercury for a Maxwellian EEDF has been calculated by Van Dijk et al [15] (…”
Section: Electron Particle Balancementioning
confidence: 99%
See 1 more Smart Citation
“…For more details about the theory that underlies this technique and the calculation of the radiative and energy loss terms, we refer to [85]. References [85,87] demonstrate an application of this technique to mercury plasma with high degrees of ionization.…”
Section: Collisional-radiative Modellingmentioning
confidence: 99%
“…The fluid model consists of a set of fluid equations for electrons, ions (Hg þ , Ar þ , and Ne þ ), and excited state neutrals such as Hg à ( 3 P 1 ), Hg à ( 1 P 1 ), Hg à ( 3 P 0 ), Hg à ( 3 P 2 ), Hg Ãà , Ar à , and Ne à . 16,18,21) The densities of charged particles are coupled self-consistently with Poisson's equation. The Hg, Ar, and Ne gas densities are assumed to be uniformly distributed according to a specified neutral pressure in the FFL.…”
Section: Fluid Modelmentioning
confidence: 99%